High-flux ultrafiltration membrane with open porous hydrophilic structure using dual pore formers. (July 2019) - Alayande, Abayomi Babatunde; Obaid, M.; Yu, Hye-Weon; Kim, In S.
Abstract: This work investigated the synergistic effect of polyvinylpyrrolidone (PVP) and hydroxypropyl-beta-cyclodextrin (HP-β-CD) as dual pore forming agents on the properties and performance of polysulfone (PSf) ultrafiltration membranes. A fixed concentration of PVP and varying concentrations of HP-β-CD were used to prepare the membranes using the phase inversion technique. The results showed that the inclusion of these additives in the dope solution increased its thermodynamic instability and promoted instantaneous demixing. Overall, an increase was observed in the hydrophilicity, open porous structure and mechanical strength of the membranes. Cross-flow filtration tests demonstrated that the pure water permeability of the fabricated membrane was 891 LMH bar −1, about 4.37 times higher than the pristine membrane, while bovine serum albumin (BSA) rejection was relatively constant (about 93%) for all the fabricated membranes. This work proposed that the addition of HP-β-CD and PVP as dual pore formers can produce a viable ultrafiltration membrane with improved water permeability without a middle ground on rejection potential. Highlights: Novel blended polysulfone ultrafiltration membranes were fabricated. Hydroxypropyl-beta-cyclodextrin and polyvinylpyrrolidone were used as dual pore formers. Porosity, hydrophilicity, mechanical strength, and water flux were substantially improved. No remarkable compromise was observed in the bovine serum albumin (BSA) rejection.